Порівняння протоколів VPN для організації корпоративної приватної мережі - Рябко, М. С. (ХНУРЕ, 2020)
This paper considers a comparison of the VPN protocols that are most commonly used when deploying a corporate virtual private network. An Internet-based enterprise VPN is required for the exchange of private information between physically remote equipment and employees. Building a VPN requires knowledge of the protocol features that will be used to transport and encrypt personal data. An understanding of the principles of working via the Internet and the equipment features of network participants is also required. The comparison was based on protocol characteristics such as data transfer rate, security, availability, complexity of blocking and implementation